Monoclonal antibodies for Alzheimer disease: statistical significance vs clinical efficacy - Einstein Francisco Camargos; Claudia Kimie Suemoto; Paulo Caramelli (Brazilian Society of Geriatrics and Gerontology, 2024)
None.